Reproductive efficiency of nellore (Bos indicus) cows subject to both ftai and homeopathic supplementation - Souto, Paulo Francisco Maciel Póvoas (2019)
The aim of this work was to determine the effect of homeopathic supplementation on both ovarian dynamics and conception rate in Nellore cows subjected to fixed-time artificial insemination (FTAI). Cows (n = 150) were randomly distributed to the control (CG) and the homeopathy group (HG). The HG cows were supplemented with Pró-cio in the mineral salt for 60 days and both experimental groups were further subjected to FTAI. Cows were evaluated for ovarian dynamics (n = 16), progesterone (P4) concentration (n = 16), and conception rates (n = 150). Ovarian dynamics determined by ultrasonography and showed similar findings for CG and HG, respectively. Thus follicular diameter (8.7 Â± 1.0 mm vs. 10.0 Â± 0.8 mm), mean pre-ovulatory follicle volume (0.46 Â± 0.15 mL vs. 0.61 Â± 0.12 mL), and mean follicular growth (3.65 Â± 1.41 mm vs. 4.60 Â± 1.21 mm) did not differ between groups. Moreover, corpus luteum diameter was similar between groups (CG: 16.28 Â± 0.7 mm vs. HG: 15.6 Â± 0.8 mm; P > 0.05), although P4 levels did differ (CG: 2.55 Â± 0.85 ng mL-1 vs. HG: 6.52 Â± 1.19 ng mL-1; P < 0.05). The conception rate after FTAI was not affected by homeopathic supplementation (CG: 74.67 %, and did HG: 77.33 %; P > 0.05). In conclusion, the homeopathic supplementation Pró-cio increases P4 concentrations but does improve the reproductive efficiency of Nellore cows subject to FTAI.